Tug of war - Lingard, Joan. (New York : Lodestar Books, 1990)
Follows the ordeal of fourteen-year-old twins Astra and Hugo Petersons, as they and their family flee their native Latvia before the advancing Russian armies in late 1944 and find themselves homeless refugees in a war-torn Germany.
"Originally published in Great Britain in 1989 by Hamish Hamilton Children's Books"--T.p. verso.
Junior High School Library Catalog (Wilson)
*Horn Book*
Booklist
7.5
7-10
Keywords: World War, 1939-1945 -- Latvia -- Juvenile fiction; World War, 1939-1945 -- Latvia -- Fiction; Refugees -- Fiction; World War, 1939-1945 -- Germany -- Fiction; World War, 1939-1945 -- Fiction; Refugees -- Fiction